2005
DOI: 10.4315/0362-028x-68.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acidified Sodium Chlorite Treatments in Reducing Escherichia coli O157:H7 on Chinese Cabbage

Abstract: Efficacy of acidified sodium chlorite for reducing the population of Escherichia coli O157:H7 pathogens on Chinese cabbage leaves was evaluated. Washing leaves with distilled water could reduce the population of E. coli O157:H7 by approximately 1.0 log CFU/g, whereas treating with acidified chlorite solution could reduce the population by 3.0 log CFU/g without changing the leaf color. A similar level of reduction was achieved by washing with sodium chlorite solution containing various organic acids. However, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 23 publications
2
49
0
Order By: Relevance
“…The same study reported the poor performance of selective medium in recovering E. coli O157:H7 from chemically treated vegetable samples (Inatsu et al, 2005a).…”
Section: Efficacy Of Combining Chlorine Disinfectants With Physicalmentioning
confidence: 99%
See 2 more Smart Citations
“…The same study reported the poor performance of selective medium in recovering E. coli O157:H7 from chemically treated vegetable samples (Inatsu et al, 2005a).…”
Section: Efficacy Of Combining Chlorine Disinfectants With Physicalmentioning
confidence: 99%
“…The ineffectiveness of sonication in improving the efficacy of chlorine water has also been reported (Inatsu et al, 2005a).…”
Section: Efficacy Of Combining Chlorine Disinfectants With Physicalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few studies have been performed to apply the bactericidal effect of ASC for the surface washing of raw vegetables or fruits 18,34 . We constructed a sensitive detection system for injured bacteria 20 and evaluated the effectiveness of ASC in killing E. coli O157:H7 on leafy vegetables with a view to its potential application to foods and food contact surfaces as an anti-microbial treatment 22 . Chinese cabbages were cut into 3 × 3 cm pieces and 400 g of leaf pieces were dipped into 1,200 mL of an inoculum cocktail containing four E. coli O157:H7 strains.…”
Section: Sanitation Of the Attached Bacteria On The Surface Of Raw Vementioning
confidence: 99%
“…The sole ingredients in sauerkraut, the cabbage, are rich in vitamins (C and K), boost the immune system and have other beneficial effects 3 . Fermentation of the cabbage juice could enhance the bacteriostatic effect of the cabbage juice as acidified sodium chloride may be formed from the ferment 5 . Such juice may have potential for extended use in the bio preservation of other foods and also has been reported to be used traditionally in the treatment of lung diseases 6 .…”
Section: Introductionmentioning
confidence: 99%